On-board microgrids for the More Electric Aircraft: technology review - Buticchi, Giampaolo; Bozhko, Serhiy; Liserre, Marco; Wheeler, Patrick; Al-Haddad, Kamal (IEEE, 2018)
This paper presents an overview of technology related to on-board microgrids for the More Electric Aircraft. All aircraft use an isolated system, where security of supply and power density represent the main requirements. Different distribution systems (AC and DC) and voltage levels coexist, and power converters have the central role in connecting them with high reliability and high power density. Ensuring the safety of supply with a limited redundancy is one of the targets of the system design, since it allows increasing the power density. This main challenge is often tackled with proper load management and advanced control strategies, as highlighted in this paper.